Sineancylus, nom. nov.: A replacement name for anancylus Gutiérrez Gregoric, 2012 (Gastropoda, Ancylidae) - Gutierrez Gregoric, Diego Eduardo (2014)
Nestor Cazzaniga (Universidad Nacional del Sur, Argentina) and Philippe Bouchet (Museum National d’Histoire Naturelle, France) have kindly advised me of homonymy in the generic name Anancylus Gutiérrez Gregoric, 2012, proposed for an Ancylidae from Iguazú National Park, Argentina (Gutiérrez Gregoric, 2012: 109). The name is preoccupied by Anancylus Thomson, 1864 (Coleoptera, Cerambycidae) (Neave, 2005). Thus, in accordance with Articles 53.3 (“Homonyms in the genus group”) and 60 (“Replacement of junior homonyms”) of the International Code of Zoological Nomenclature (ICZN, 1999), I propose the replacement name Sineancylus, nom. nov.